Financial Literacy and Investment Practices of Individual Investors in Pokhara - Sapkota, Ram (Academia Research Journal, 2024)
This study empirically investigates the financial literacy and investment practices of individual investors in Pokhara. Through liberalization, privatization, and globalization, Nepal's economy has grown and financial markets have expanded, opening the door to an abundance of financial products that can be used as credit or as an investment alternative. This paper assesses the preference of the investment area by the investors. First this paper examines the differences in different investment aspects such as investment horizon, type of investors, investment objectives, expectation of return and their preference by demographic features of investors. Second this paper assesses the regress of financial literacy on investment horizon, investment objectives, expectation of return and their preference. According to the findings, Investor who has liquidity as investment objectives expect 10 to 50% return from their investment. Investors who have moderate and low risk taking objectives are expecting 5-10% return. From the study it is found that male respondent has high financial literacy than female respondent. It is found that individual investor who has high financial literacy they prefer to invest in short period of time and investors who have less financial literacy prefers long period of time as investment. Investor also shown good interest regarding the investment in business rather than other, but there is no significant relationship between gender, marital status and this opinion.